An Exploratory Study of Entrepreneurship in Taiwan’s Small & Medium Enterprises – Case Studies of Six Manufacturing Companies - Tsai, Wen-Chia (Information Management and Business Review, 2014)
Entrepreneurship with organization setting has been conceptualized in a variety of ways. Studies in this area remain broad and appear relatively fragmented. From previous literature reviews, we found that little attention has been paid toward the entrepreneurial management model with the starting-up phases of Small & Medium Enterprises (SMEs) in Taiwan. In view of this, the purpose of this study is to fill this gap in the literature by proposing a research framework that integrates both entrepreneurship literature and Small & Medium Enterprises (SMEs) literature. To address this problem, a new research method based on integrating cases study and in-depth interviews methods are also proposed. According to the results, the individual factor was the central part among the four contributing factors (reproduction, imitation, valorization, and venture). With respect to the six dimensions of entrepreneurship (strategic orientation, commitment to opportunity, commitment to resources, control over resources, management frame, and compensation philosophy), the enterprises interviewed in this research all set forth their perspectives. As for the four kinds of entrepreneurial status, there were four entrepreneurial imitation companies and two entrepreneurial venture companies in this research. To conclude, several propositions were proposed, and the results released that the individual factor was the crucial part among the four contributing factors. Research also examined the main dimensions of entrepreneurship for analyzing the theoretical basis.